Lactobacillus rhamnosus GG for Cow's Milk Allergy in Children: A Systematic Review and Meta-Analysis - Tan, Weifu; Zhou, Zhicong; Li, Wei; Lu, Han; Qiu, Zemin (Frontiers in Pediatrics, 2021)
Objective: Cow’s milk allergy (CMA) is a common allergic disease. Probiotics have been suggested as a treatment for CMA, and Lactobacillus rhamnosus GG (LGG) is one of the important probiotics. Some reports explore this topic; however, the application in CMA remains to be firmly established. Methods: To assess the effects of LGG on CMA in children, the PubMed/Medline, Embase, Cochrane Library and Web of Science databases were searched for studies published in the English language. Results: Nine studies were finally identified. Significantly higher tolerability rate of LGG favoring LGG over controls were observed (risk ratio [RR] was 4.44; 95% confidence interval [CI] was 2.74 to 7.18; I2=0.00; moderate-quality evidence). No significant differences in SCORAD values favoring LGG over the placebo (mean difference [MD]was 1.41; 95%CI, −4.99 to 7.82; P =0.67; very low-quality evidence) but LGG had significant effect on the improvement of fecal occult blood (RR was 0.36; 95%CI was 0.14 to 0.92; P = 0.03; low-quality evidence). Conclusion: Nine studies were finally identified. Significantly higher tolerability rate of LGG favoring LGG over controls were observed (risk ratio was 2.22; 95% confidence interval was 1.86 to 2.66; I2=0.00; moderate-quality evidence). No significant differences in SCORAD values favoring LGG over the placebo (mean difference was 1.41; 95%CI, −4.99 to 7.82; P =0.67; very low-quality evidence) and LGG may had effect on the improvement of fecal occult blood (risk ratio was 0.36; 95%CI was 0.14 to 0.92; P = 0.03; low-quality evidence).